Disruption of nuclear factor (erythroid‐derived‐2)‐like 2 antioxidant signaling: a mechanism for impaired activation of stem cells and delayed regeneration of skeletal muscle. Issue 5 (2nd February 2016) - Shelar, Sandeep Balu; Narasimhan, Madhusudhanan; Shanmugam, Gobinath; Litovsky, Silvio Hector; Gounder, Sellamuthu S.; Karan, Goutam; Arulvasu, Cinnasamy; Kensler, Thomas W.; Hoidal, John R.; Darley‐Usmar, Victor M.; Rajasekaran, Namakkal S.
Abstract : Recently we have reported that age‐dependent decline in antioxidant levels accelerated apoptosis and skeletal muscle degeneration. Here, we demonstrate genetic ablation of the master cytoprotective transcription factor, nuclear factor (erythroid‐derived‐2)‐like 2 (Nrf2), aggravates cardiotoxin (CTX)‐induced tibialis anterior (TA) muscle damage. Disruption of Nrf2 signaling sustained the CTX‐induced burden of reactive oxygen species together with compromised expression of antioxidant genes and proteins. Transcript/protein expression of phenotypic markers of muscle differentiation, namely paired box 7 (satellite cell) and early myogenic differentiation and terminal differentiation (myogenin and myosin heavy chain 2) were increased on d 2 and 4 postinjury but later returned to baseline levels on d 8 and 15 in wild‐type (WT) mice. In contrast, these responses were persistently augmented in Nrf2‐null mice suggesting that regulation of the regeneration‐related signaling mechanisms require Nrf2 for normal functioning. Furthermore, Nrf2‐null mice displayed slower regeneration marked by dysregulation of embryonic myosin heavy chain temporal expression. Histologic observations illustrated that Nrf2‐null mice displayed smaller, immature TA muscle fibers compared with WT counterparts on d 15 after CTX injury. Improvement in TA muscle morphology and gain in muscle mass evident in the WT mice was not noticeable in the Nrf2‐null animals. Taken together these data show that the satellite cell activation, proliferation, and differentiation requires a functional Nrf2 system for effective healing following injury.—Shelar, S. B., Narasimhan, M., Shanmugam, G., Litovsky, S. H., Gounder, S. S., Karan, G., Arulvasu, C., Kensler, T. W., Hoidal, J. R., Darley‐Usmar, V. M., Rajasekaran, N. S. Disruption of nuclear factor (erythroid‐derived‐2)—like 2 antioxidant signaling: a mechanism for impaired activation of stem cells and delayed regeneration of skeletal muscle. FASEB J. 30, 1865–1879 (2016). www.fasebj.org